AB0005 F1 Hybrid of NZW and Fcg Riib-Deficient B6 Mice Developed Phenotype Conversion from Rheumatoid Arthritis to Murine Lupus. (10th June 2014) - Amano, H.; Kaneko, T.; Lin, Q.; Shinya, K.; Nishikawa, K.; Hirose, S.; Takasaki, Y.
Abstract : Background: FcγRIIB negatively regulates BCR-mediated activation signals. We previously established an FcγRIIB-deficient B6-congenic mouse strain (KO1) by gene targeting in 129-derived embryonic stem cells followed by backcrossing to B6 mice. KO1 spontaneously developed pathology of rheumatoid arthritis (RA) with autoantibody production and pannus formation leading to joint destruction. Objectives: To analyse the phenotypic change of KO1 by crossing with lupus prone New Zealand White (NZW) mice, we established the F1 hybrid of KO1 and NZW mice. Also we analysed (KO1 x NZW) F2 mice to see the sharing loci contributing to disease phenotypes. Methods: We analysed the (KO1 x NZW) F1 mice and (KO1 x NZW) F2 mice. Serum levels of RF, IgG antibodies against double-stranded DNA and chromatin were measured using ELISA. The severity of renal disease was monitored by biweekly testing for proteinuria. Histopathological examination was also performed. Results: The F1 hybrid of these mice developed glomerulonephritis with the high incidence of positive anti- double-stranded DNA and chromatin antibodies. They did not develop the phenotype of RA, but developed lupus phenotype associated with the inflammatory infiltration in salivary glands as observed in Sjögren syndrome. In the progeny of (KO1 x NZW) F2 mice, RA, SLE, and Sjögren syndrome developed independently or overlapped in an individual mouse. We found that the B6-derived locus located in the centromeric region on chromosome 12 was significantly associated with all these disease phenotypes, suggesting that this locus may play a role in common process shared by these diseases. Conclusions: Phenotypic specificity of murine autoimmune disorder depends on the genetic factors sharing RA, SLE, and Sjögren syndrome. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6071